Result Comparison of Fecal Occult Blood Test between FOBT Hb and FOBT Hb tambah Tranferrin in Detecting Upper Gastrointestinal Tract Bleeding - Anik Widijanti; Sri Sulistiandari; Tony Hariyanto; Rahma Triliana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Immunological fecal occult blood test (FOBT) using anti human hemoglobin (Hb) has a low sensitivity in detecting upper gastrointestinal (GI) bleeding, due to Hb degradation. Transferrin (Tf) is more stable in stool when compared to Hb, provides an alternatives on diagnosing upper GI bleeding. This study aim to determine the advantage of FOBT Hb + Tf in detecting upper GI bleeding compared with FOBT Hb alone. Method: This study was conducted by comparing the diagnostic value of Rapid Immunochromatographic FOBT that use anti-human Hb alone, with the one using combination of anti human Hb Tf simultaneously in detecting upper GI bleeding. Stool sample from 48 patients with upper GI bleeding and 29 controls (without any upper GI bleeding) were collected then tested with both FOBT Methods. Endoscopy study was used as gold standard endoscopy to determine test’s diagnostic value. Result: In detecting upper GI bleeding, the sensitivity of FOBT Hb + Tf (85.42%) was higher than FOBT Hb (29.17%). The specifity of both Methods were accurate at 89.66% and 93.10% respectively. Positive predictive values (PPV) for both Methods were also good at 93.18% and 87.50% while negative predictive value (NPV) FOBT Hb + Tf (78.79%) were higher than FOBT Hb (44.26%). Conclusion: Between these two test Methods on detecting upper GI bleeding, FOBT Hb + Tf has higher sensitivity, PPV and NPV value compared to FOBT Hb. It is advisable to use FOBT Hb + Tf for upper GI bleeding screening. Keywords: FOBT, immunochromatography, hemoglobin, transferrin, upper GI bleeding